The obligation to rehabilitate mining areas : post mining activities - Madalane, Thembi (University of Limpopo (Turfloop Campus), 2012)
The study focuses on rehabilitation, since absence of proper rehabilitation process result in indelible damage to the environment. South Africa, like many other countries, is faced with many environmental problems caused by mining. These problems are particularly caused by, inter alia, abandoned mining areas without rehabilitation, inadequate environmental impact assessment after closure, inadequate financial provision for rehabilitation, and lack of monitoring and aftercare system after post mine closure. The study found that many Companies ignore laws governing prospecting, extraction and rehabilitation. The main purpose of this research is to investigate and recommend guidelines in the rehabilitation process so as to instil respect for the environment. The study therefore recommended strict legislation relating to environmental protection against mining.
Thesis (LLM) -- University of Limpopo, 2012
Keywords: Mines rehabilitation; Mining areas; Post mining activities; 622.40968; Mineral industries -- Environmental aspects; Environmental protection -- South Africa; Environmental law; Mines and mineral resources -- South Africa